Congratulations to the Danish People’s Party! - Kosiara-Pedersen, Karina (Politica, 2020)
The Danish People’s Party is the successful splinter party of the Progress Party created by Pia Kjærsgaard and collaborators in 1996. Traditional party membership, public financing, and a high degree of centralization and party discipline characterize the party organization, while their political program emphasizes less immigration and integration, more law and order, and welfare chauvinism. Their first 25 years have been successful. Their electoral success has affected government formation and policies. They have provided the parliamentary base for center-right governments and gained political concessions, particularly in the immigration and integration field. While aiming to become an influential party, they did not enter into government when they became the largest party right of centre in 2015. Since then their electoral support has waned.